Penerapan Akuntansi Manajemen dalam Optimalisasi Pengelolaan Keuangan UMKM Es Teh Poci Labang - Fajri Anggy Efendi; Muhammad Maulana Ardiansyah; Eka Wahyu Purwatiningsih; Alung Febri Permadani; Anisah Choirunnisa; Afiatus Syifa; Mochamad Reza Adiyanto (Pusat Riset dan Inovasi Nasional, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the Indonesian economy, but often face challenges in effective financial management. often face challenges in effective financial management. This research This study aims to analyse the application of management accounting in increasing turnover, net profit, and cash management in Labang Iced Tea Pot MSMEs in Bangkalan Regency, East Java. Bangkalan Regency, East Java. The research method used is descriptive qualitative, with data obtained through interviews, observation, and documentation. documentation. The results showed that the application of management accounting helps Labang Iced Tea Poci in determining the optimal selling price, managing cash flow, and increasing the efficiency of operational costs. cash flow, and improve operational cost efficiency. By analysing the break-even point, budget management, and recording break-even analysis, budget management, and systematic financial recording, this MSME is able to increase net profit to Rp 254,000 per day on the able to increase net profit up to IDR 254,000 per day at certain pricing strategies. pricing strategy. In addition, structured cash management allows the business to maintain liquidity and avoid deficits. maintain liquidity and avoid operational deficits. This research concluded that management accounting plays an important role in improving financial performance and support the sustainability of MSME businesses. The implementation of management accounting not only improves the efficiency of financial management, but also serves as a foundation for better strategic decision-making. the foundation for better strategic decision-making.